International Trade Policy - Grimwade, Nigel (Taylor & Francis, 1996)
This volume provides an introduction to the basic theory behind international trade policy. The author analyses current policy issues within a theoretical framework. The book adopts a thematic approach, with each chapter examining a different issue - each of which is of central importance to contemporary trade policy. The book will be essential for all those who want to understand what governments do, in terms of trade policy and how they do it.